Crossing Over, Moving Over: Personal Narratives of Caribbean Adult College Women’s Struggles and Strategies - Gwendoline Regina James (Adult Education Research Conference, 2006)
This research study documented the personal narratives of Caribbean immigrant college women’s struggles and strategies as they adjusted to life in the United States. The main purpose of the study was to examine the extent to which the concurrent work, family and community settings impact their personal and cognitive development.
Keywords: Cognitive development; social impact; minority women